Usability Flaws in Medication Alerting Systems: Impact on Usage and Work System - Marcilly, R.; Ammenwerth, E.; Roehrer, E.; Pelayo, S.; Vasseur, F.; Beuscart-Zéphir, M.-C. (Yearbook of Medical Informatics, 2015)
Objectives: Previous research has shown that medication alerting systems face usability issues. There has been no previous attempt to systematically explore the consequences of usability flaws in such systems on users (i.e. usage problems) and work systems (i.e. negative outcomes). This paper aims at exploring and synthesizing the consequences of usability flaws in terms of usage problems and negative outcomes on the work system.Methods: A secondary analysis of 26 papers included in a prior systematic review of the usability flaws in medication alerting was performed. Usage problems and negative outcomes were extracted and sorted. Links between usability flaws, usage problems, and negative outcomes were also analyzed.Results: Poor usability generates a large variety of consequences. It impacts the user from a cognitive, behavioral, emotional, and attitudinal perspective. Ultimately, usability flaws have negative consequences on the workflow, the effectiveness of the technology, the medication management process, and, more importantly, patient safety. Only few complete pathways leading from usability flaws to negative outcomes were identified.Conclusion: Usability flaws in medication alerting systems impede users, and ultimately their work system, and negatively impact patient safety. Therefore, the usability dimension may act as a hidden explanatory variable that could explain, at least partly, the (absence of) intended outcomes of new technology.
Keywords: Human engineering; decision support system; clinical; review; usability; usage; patient safety; alerting functions